semiosis - as a generator of meaning in the creative literary text - Taher, Nizar S. (Humanities Journal of University of Zakho, 2018)
The purpose of this study is to show how semiosis is produces for the purpose of producing or generating semantics in the creative literary text. Because the process, analysis of the signs in the creative texts and it helps the researcher to reach the inner textures and find hidden significance Despite the importance of this theme (Semios) for the production of signs, on the other hand, there are no research or academic study in the Kurdish literary criticism on this subject. In this piece of study, which title of semiosis - as a generator of meaning in the creative literary text we conduct the poem of - Baran - off by Muhammad Ali Yasin Taha - as example the theme of the semiosis in terms of content in general and we explained the concept and definition of the semi- We also explained the location of the semiosis and its elements and how it works within the Simeologic theory. Then we explained the two signs (Baran, Yar) of the poem mentioned by the semiosis way of producing significance. It was clear to us that the majority of the hidden significance of the poem was embodied In these two parameters (Baran, Yar) and especially the tag (Baran) embraces the proportion greater than the other.